The 14th International Conference on Microelectronics,
DOI: 10.1109/icm-02.2002.1161546
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of total ionizing dose radiation effects on MOS capacitor

Abstract: Egypt. Tel (202) 7585867 Ext. 1, Fax (202) 7585835/38 Ext. 458, skayed@ieee.org ABSTRACTThe aim of this paper is to investigate the total ionizing dose (TID) radiation effects on MOS capacitor wafer samples that are locally fabricated for this purpose. The oxide was prepared by dry-wet -dry oxidation technique at 1000 C o using N -type Si substrate of about 3 Ω.cm. The samples have been exposed to irradiation at different doses from 1Krad(SiO 2 ) up to 1Mrad(SiO 2 ) using two different Gamma sources for high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The transfer characteristics, output characteristics, drainsource resistance (R ds ), blocking characteristics, and gate-lag characteristics of the devices before and after TID irradiation were measured by using semiconductor device analyzers (models: Agilent B1505A and Agilent B1500A). Shelf annealing (annealing at RT) [14] was also measured after TID irradiation. Furthermore, SR785 dynamic signal analyzer was used to measure LFNs, while filter and amplifier units were provided by Proplus 9812B.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer characteristics, output characteristics, drainsource resistance (R ds ), blocking characteristics, and gate-lag characteristics of the devices before and after TID irradiation were measured by using semiconductor device analyzers (models: Agilent B1505A and Agilent B1500A). Shelf annealing (annealing at RT) [14] was also measured after TID irradiation. Furthermore, SR785 dynamic signal analyzer was used to measure LFNs, while filter and amplifier units were provided by Proplus 9812B.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Sun et al [9] investigated that GaN HEMTs which are with Schottky metallic gate structures typically exhibit a small shift after TID irradiation, while GaN HEMTs with MOS gates exhibit additional threshold voltage shift compared to similar devices with Schottky gates because of hole trapped in the gate oxide. Lidow et al [10] have studied the E-mode Schottky gate devices and concluded that the devices exhibited drifts of ∼0.2 V. Ives et al [11] have investigated the commercial radio frequency (RF) D-mode Schottky gate power HEMTs and indicated that the devices exhibited shifts of about 0.15 V. On the other hand, although significant progress has been made in understanding the underlying physics of TID irradiation in the Si MOSFETs [12][13][14][15][16][17][18][19], there is not much work undertaken on the TID effects in the Cascode GaN HEMTs. Chen et al [20] have investigated the high and low dose-rate radiation damage effects of the Cascode structure GaN power devices and found that the threshold voltage of the Cascode device was negatively drifted, having no enhanced low dose rate sensitivity effect.…”
Section: Introductionmentioning
confidence: 99%